Extensive primary oral malignant melanoma: A case report with review of literature - Walid Bijou; Mohammed Laachoubi; Youssef Oukessou; Sami Rouadi; Reda Abada; Mohamed Roubal; Mohamed Mahtar (Elsevier, 2022)
Oral mucosal melanoma is an exceptionally rare tumor with the tendency to metastasize and locally invade tissues more readily than other malignant tumor of the oral cavity. Here we present a case of 53-year-old women patient with chief complaint of a discoloration over the hard palate since 6 months. On the basis of a through clinical and paraclinical assessment, a diagnosis of oral malignant melanoma was evoked. On histopathological and immunohistochemical analysis with S-100 and homatropine methylbromide 45 the diagnosis of malignant melanoma of the had palate was confirmed.